2022
DOI: 10.3389/fpls.2022.941061
|View full text |Cite
|
Sign up to set email alerts
|

Daily changes on seasonal ecophysiological responses of the intertidal brown macroalga Lessonia spicata: Implications of climate change

Abstract: Global climate change is expected to have detrimental effects on coastal ecosystems, with impacts observable at the local and regional levels, depending on factors such as light, temperature, and nutrients. Shifts in dominance between primary producers that can capitalize on carbon availability for photosynthesis will have knock-on effects on marine ecosystems, affecting their ecophysiological responses and biological processes. Here, we study the ecophysiological vulnerability, photoacclimation capacity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…Responses of the xanthophyll cycle could reflect a regulatory and photoprotective mechanism that downregulates the delivery of excitation energy into the electron transport chain to match the rates at which products of electron transport can be consumed in these algae (Demmig- Adams and Adams, 2006). In our study, significant Macroalgae can also display phenotypic plasticity, which includes the presence of PCs in brown macroalgae (Goḿez and Huovinen, 2020;Celis-Pláet al, 2022) and MAAs in red seaweeds (Oren and Gunde-Cimerman, 2007;De la Coba et al, 2009). Our findings showed that, in M. hariotii and P. endiviifolia, the concentration of PCs increased at elevated temperatures over time.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Responses of the xanthophyll cycle could reflect a regulatory and photoprotective mechanism that downregulates the delivery of excitation energy into the electron transport chain to match the rates at which products of electron transport can be consumed in these algae (Demmig- Adams and Adams, 2006). In our study, significant Macroalgae can also display phenotypic plasticity, which includes the presence of PCs in brown macroalgae (Goḿez and Huovinen, 2020;Celis-Pláet al, 2022) and MAAs in red seaweeds (Oren and Gunde-Cimerman, 2007;De la Coba et al, 2009). Our findings showed that, in M. hariotii and P. endiviifolia, the concentration of PCs increased at elevated temperatures over time.…”
Section: Discussionmentioning
confidence: 67%
“…The 2,2-diphenyl-1-picrylhydrazyl (DPPH) method was used as a proxy for determining total antioxidant capacity; the same extracts used for PC determination were used for the total antioxidant capacity assessment (Celis-Pláet al, 2022). Each extract (150 mL) was added to a stock solution of DPPH (1.27 mM concentration; 90 MeOH:10 H 2 O), and the reaction was completed after 30 min in the dark at an ambient temperature (~20°C); the absorbance was read at 517 nm using a microplate reader.…”
Section: Total Antioxidant Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Lessonia berteroana is widely distributed on hard bottoms in northern Chile [5]. It is an economic and social resource species, common in the intertidal and shallow subtidal zone [6], and has been previously used for biomonitoring through bioaccumulation [7], abundance and morphometric features, fertility and sporophyte formation [8], and ecophysiological traits [9,10]. Microalga biomass is one of the most commonly used attributes in water quality monitoring studies, as it consistently responds to stressors [11] but also serves as an early warning system [12].…”
Section: Introductionmentioning
confidence: 99%